2020
DOI: 10.1088/1757-899x/709/2/022041
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and optimization of vacuum assisted resin infusion process for large-sized structures made of carbon fiber-reinforced plastics

Abstract: Vacuum assisted resin infusion (VARI) is a process applied to manufacture large structures of composite materials, such as aircraft wing and fuselage skins, but the process parameters are designed by experience or lots of experiments. In this paper, the filling process of VARI for composite fuselage skin was analyzed based on simulation and optimized location of resin inlet ports. Firstly, we made 3D model of fuselage skin and simulated impregnation process. Secondly, we determined the location and quantity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Based on the results obtained, it can be concluded that the errors of the target parameters arise from the simulation complexity of the manufacture of products from composite materials by injection molding methods, requiring the consideration of many factors. The most signifi cant ones are bulk polymerization of the binder and change of its viscosity in the process of compounding and impregnation, the fabric pliability and permeability of the fi brous preform, as demonstrated in papers [12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results obtained, it can be concluded that the errors of the target parameters arise from the simulation complexity of the manufacture of products from composite materials by injection molding methods, requiring the consideration of many factors. The most signifi cant ones are bulk polymerization of the binder and change of its viscosity in the process of compounding and impregnation, the fabric pliability and permeability of the fi brous preform, as demonstrated in papers [12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…The numerical simulation of the resin infusion process involves the modeling of the resin flow through the reinforcement and the crosslinking reaction of the resin [8]. The resin flow through the fiber reinforcement is modeled by Darcy's law [32]:…”
Section: Mathematical Models For Numerical Simulationmentioning
confidence: 99%
“…The research in composite materials is very active both on the development of multifunctional, nanostructured, or environmentally friendly composite materials and on the technological challenges in fabrication and characterization [6]. Since the production of large, complex, and high-performance FRP structures at low costs is challenging, in recent years, a family of processes, named liquid composite molding (LCM), progressed toward new solutions with the aim of reducing costs and cycle times, thus becoming attractive for aeronautic applications as an alternative to conventional autoclave-based processes [7,8]. In LCM processes, prepregs are replaced by dry fiber preforms, i.e., an assembly of dry fibers plies that have been pre-shaped to the form of the desired product [9,10], which must be impregnated with resin, either via resin transfer molding (RTM), at pressure higher than 1 bar, or liquid resin infusion (LRI), just under vacuum [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…E3S Web of Conferences 376, 01017 (2023) https://doi.org/10.1051/e3sconf/202337601017 ERSME-2023 Composite materials have high values of specific strength and rigidity, fatigue life, can be operated in a wide temperature range, have a low temperature coefficient of linear expansion, and also have a relatively low density, which greatly expands the technological possibilities of their application [1][2][3][4] and, therefore, the use of composite materials. materials becomes one of the most important factors determining the competitiveness of manufactured products [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%